The Cerros de Aguirre Formation: Evidence of Vendian Magmatism in Uruguay (Latin American Journal of Sedimentology and Basin Analysis, 2021)
This paper deals with the stratigraphy, petrography, geochemistry and structural relationships of the Cerros de Aguirre Formation, which is located in the Cuchilla Dionisio Terrane in eastern Uruguay (Bossi et al., 1998; Bossi and Gaucher, 2004) (Fig. 1). Detailed mapping at 1:20,000 scale, thin section petrography and geochemistry of major and trace elements were applied in this study.The Cerros de Aguirre Formation is mainly composed of pyroclastic rocks with some interbedded volcanic layers, cropping out with a roughly elliptical outline 16 x 4 km in size, with a major axis oriented northsouth (Fig. 2). The Cerros de Aguirre Formation unconformably overlies granulites of the Chafalote suite (Masquelín et al., 2001). To the east, it is in tectonic contact along a regional shear zone with the greenschist-facies metasediments of the Rocha Group (Hasui et al., 1975).The Cerros de Aguirre Formation is subdivided here into three units: a) volumetrically dominant, finegrained fall deposits; b) concordant lavas, intercalated with the fall deposits, and c) pyroclastic flows. Pyroclastic rocks include finely banded tuffs, massive tuffs, lapilli tuffs and tuffites with geochemical compositions ranging from andesites to rhyolites. Lava flows are represented by basalts, andesi-basalts and rhyolites. Pyroclastic flows are 20 to 100 m thick and up to 2 km wide, showing andesitic to rhyolitic compositions.The whole assembly exhibits open folding showing N20-30E oriented, sub-vertical axial planes (Figs. 2 and 3). Deformation increases in intensity toward the east, the main structure being an asymmetric syncline truncated in its eastern flank by a shear zone that also constitutes the western boundary of the Rocha Group (Fig. 3).Geochemistry and field work, both supports a syngenetic origin for lavas and fall deposits. The pervasive carbonation affecting the unit is analyzed, showing evidences that suggest that the process is simultaneous with volcanism. Measured LOI values of up to 11.3 % are due to carbonate cementation of porous pyroclastites. Whereas this process substantially altered major element compostion of volcanic and pyroclastic rocks, their primary trace element and especially REE composition has been preserved. This is demonstrated by the absence of correlation between REE patterns (Fig. 7) and LOI or lithology. Volcanic rocks show strong compositional variation, between basalt and rhyolite, with no evident compositional gap. Basalt flows occurring at the base and top of the unit do not differ petrographically or geochemically, implying that basaltic magmatic pulses intercalated with pyroclastic rocks generated by more felsic volcanism. Two possibilities are envisaged to account for the above mentioned facts: 1) different magmatic rocks are the product of differentiation of a single source, or 2) volcanism was bimodal, but intermediate terms were generated by magma mixing mechanisms. The latter explanation is more consistent with the observed characteristics of basalts occurring at several levels in the Cerros de Aguirre Formation.Based on the syngenicity of volcanic rocks and fall deposits, available U-Pb SHRIMP ages for andesites occurring at the top of the Cerros de Aguirre Formation (571 ± 8 Ma, Hartmann et al., 2002) can be considered representative of the whole volcanic event.Regarding its geotectonic setting, the Cerros de Aguirre Formation could record a late extensional episode of the Brazilian orogeny, perhaps related to the opening of the Arroyo del Soldado basin (Gaucher, 2000), although Blanco and Gaucher (2005) argue for an older age for rifting in the latter unit. Regardless the relationship of these extensional events, deformation exhibited by both the Cerros de Aguirre Formation and the Arroyo del Soldado Group seems to be of the same age and related to a regional sinistral transpressive event.